A new antigen SUMI carried on glycophorin A encoded by the GYPA*M with c.91A>C (p.Thr31Pro) belongs to the MNS blood group system. Issue 6 (1st May 2020) - Ito, Shoichi; Kaito, Sayaka; Miyazaki, Toru; Kikuchi, Go; Isa, Kazumi; Tsuneyama, Hatsue; Kurita, Ryo; Ogasawara, Kenichi; Uchikawa, Makoto; Satake, Masahiro
Abstract : BACKGROUND: MNS is one of the highly polymorphic blood groups comprising many antigens generated by genomic recombination among the GYPA, GYPB, and GYPE genes as well as by single‐nucleotide changes. We report a patient with red blood cell (RBC) antibody against an unknown low‐frequency antigen, tentatively named SUMI, and investigated its carrier molecule and causal gene. STUDY DESIGN AND METHODS: Standard serologic tests, including enzyme tests, were performed. Monoclonal anti‐SUMI–producing cells (HIRO‐305) were established by transformation and hybridization methods using lymphocytes from a donor having anti‐SUMI. SUMI+ RBCs were examined by immunocomplex capture fluorescence analysis (ICFA) using HIRO‐305 and murine monoclonal antibodies against RBC membrane proteins carrying blood group antigens. Genomic DNA was extracted from whole blood, and the GYPA gene was analyzed by polymerase chain reactions and Sanger sequencing. RESULTS: Serologic screening revealed that 23 of the 541, 522 individuals (0.0042%) were SUMI+, whereas 1351 of the 10, 392 individuals (13.0%) had alloanti‐SUMI. SUMI antigen was sensitive to ficin, trypsin, pronase, and neuraminidase, but resistant to α‐chymotrypsin and sulfydryl‐reducing agents. ICFA revealed that the SUMI antigen was carried on glycophorin A (GPA). According to Sanger sequencing and cloning, the SUMI+ individuals had a GYPA*M allele with c.91A>C (p.Thr31Pro), which may abolish the O‐glycan attachment site. CONCLUSIONS: The new low‐frequency antigen SUMI is carried on GPA encoded by the GYPA*M allele with c.91A>C (p.Thr31Pro). Neuraminidase sensitivity suggests that glycophorin around Pro31 are involved in the SUMI determinant.